Ultrasound criteria for predicting pre-cancer changes of the gastric mucosa in patients with chronic atrophic gastritis combined with thyroid pathology - Yu. M. Stepanov; L. M. Mosiichuk; I. S. Konenko; O. V. Simonova; O. P. Petishko; O. M. Shevtsova; L. V. Demeshkina (Zaporožskij Medicinskij Žurnal)
Precancerous conditions increase the risk of gastric cancer by 2–3 % every 10 years. Among comorbid pathology, 46 % of all endocrinopathies are diseases of the thyroid gland. An urgent issue today is the definition of non-invasive criteria for the formation of a risk group for the detection of precancerous changes in the gastric mucosa in patients with comorbid pathology.